Urbanization, energy consumption, and pollutant emission in Asian developing economies: An empirical analysis - Ruhul A. Salim; Shuddhasattwa Rafiq; Sahar Shafiei (Asian Development Bank Institute (ADBI), 2017)
This paper aims to investigate the effects of urbanization, renewable and non-renewable energy consumption, trade liberalization, and economic growth on pollutant emissions and energy intensity in selected Asian developing countries from 1980 to 2010. We use both linear and nonlinear panel data econometric techniques and employ the recently introduced mean group estimation methods, allowing for heterogeneity and cross-sectional dependence. However, to check robustness of our panel results, we also apply the autoregressive distributed lag bound testing approach to country-level data. In addition, the relationship between affluence and CO2 emissions is examined in the context of the Environmental Kuznets Curve (EKC) hypothesis. The estimation results identify population, affluence, and non-renewable energy consumption as the main factors in pollutant emissions in Asian countries. However, the results of the EKC hypothesis show that when countries achieve a certain level of economic growth, their emissions tend to decline. Whereas nonlinear results show that renewable energy, urbanization, and trade liberalization reduce emissions, linear estimations do not confirm such outcomes. Thus, substitution of non-renewable for renewable energy consumption, as well as cautious and planned urbanization programs, and more liberal trading regimes may be viable options for the sustainable growth of these emerging Asian economies.
Keywords: Q2; E4; C33; 330; renewable energy consumption; urbanization; pollutant emissions; openness; EKC hypothesis; panel data